Peculiarities of Accounting Policy Formation in Small and Medium Enterprises - Kanapickienė, Rasa; Rauchaitė, Loreta (Ekonomika, 2003)
When Lithuania becomes a member of the EU, the business environment will change dramatically: a free trade environment will be introduced; the trading restrictions and constraints will be abolished, etc. In the new environment the individual qualities of the undertakings and the quality of the internal processes and management will become vital. Moreover, the importance of the company accounting policy, which is a measure that helps to accomplish the objectives of the company, will increase significantly. The work looks at the accounting policy concept, analyses accounting policy interpretations provided by different scientists, offers analysis of the accounting policy elements, and, based on the findings of the research, reveals the peculiarities of the accounting policy formation in small and medium enterprises. To identify the peculiarities of the accounting policy formation in small and medium enterprises, in FebruaryMarch 2003 a research was carried out in Kaunas enterprises of this type. The analysis of the research results brought to the following conclusions: Most companies acknowledge the necessity of framing the accounting policy. 24% of company representatives do not appreciate the importance of the accounting policy; however some aspects of the accounting policy are present at the said companies. The investigation of the organisational aspect of the accounting policy showed that the greatest consideration for that aspect is given by small companies. The analysis of the research result shows that: • all the companies mostly disregard the description of the accounting planning method; • all the companies pay rather great attention to drawing up the job descriptions of the accounting staff; • some company managers fail to inform their employees of the commercial secret issue. The job descriptions (employment contracts) do not contain any restrictions related to the use of information acquired at work after the termination of the employment agreement; the issue of periodical training of employees, courses and seminars was mainly addressed by the representatives of small and medium enterprises. The companies give rather great attention to the qualification level of the accounting staff. The literature which is necessary for correct tax accounting is available for the accounting staff of a vast majority of companies. The above facts show that a relevant accounting staff training system exists in the companies (except for micro ones). The investigation of the technical aspect of the company accounting policy shows that: • most of the accountants approve the list of accounts used by the company, however only a few companies have typical account correspondences approved; • to ensure that the company staff do not exceed their powers when signing the company documents, each company should have an approved list of responsible persons and the sample signatures thereof. Small and medium enterprises have achieved the best results in this field, while the micro companies give the least attention thereto; • the largest weight on the timely submission of the documents to the accounts is put in small enterprises; however only a small number of micro and medium enterprises can boast of such situation; the accounting document flow is most exactly defined in small enterprises; although most of the companies may be considered as computerised undertakings, only a few of them take care of the safety of their data; • the end-of-period procedures which arc performed before drawing up the annual financial accounting are described by only 4% of micro enterprises and 5% of small ones. However neither of the investigated medium enterprises have the said descriptions. The investigation n of the methodological aspect of the accounting policy shows that: • the accounting policies of all the companies lack perfection since the general accounting principles are described by only 13% of micro enterprises and 37% of small companies, while the medium enterprises do not have such descriptions whatsoever; • the greatest attention is given by the companies to the long-term asset accounting. Most of the investigated companies have a definition of the long-term asset depreciation method and a fixed minimum historical value of the long-tenn tangible assets; • the stock accounting and the procedures of the income I expenditure appreciation in the accounting have actually not been described by the companies; the results of the investigation show that most of the companies also fail to understand the importance of the tax policy. In summary, il can be maintained that only individual elements of accounting policy are present in small and medium companies; however the said elements arc not coherent.